Prostate-Specific Antigen Velocity Predicts Surgical Outcome of Thulium Laser Enucleation of the Prostate - Chen, Po-You; Chen, Shao-Ming; Juang, Horng-Heng; Hou, Chen-Pang; Lin, Yu-Hsiang; Yang, Pei-Shan; Chen, Chien-Lun; Chang, Phei-Lang; Lin, Kuo-Yen; Tsui, Ke-Hung (Frontiers in Medicine, 2022)
Background We determined the effect of prostate-specific antigen velocity (PSAV) on the surgical outcome of thulium laser enucleation of the prostate (ThuLEP) in patients with benign prostatic hyperplasia (BPH). Methods A retrospective review was performed of prospectively collected data of patients with BPH who underwent ThuLEP at any time from 2017 to 2019. Patients who had undergone BPH surgery or had prostate cancer previously were excluded, and patients with prostate-specific antigen (PSA) > 4 ng/mL were examined through transrectal ultrasound-guided prostate biopsy to rule out prostatic malignancy. Furthermore, patients were excluded if prostatic malignancy was diagnosed during postsurgery follow-up. Results The PSA level, international prostate symptom score (IPSS), and quality of life (QoL) of 27 male patients at 3 and 15 months postsurgery differed significantly from those at presurgery; the maximum flow rate (Qmax) and postvoid residual (PVR) significantly differed between 3 months postsurgery and presurgery; and 22 and 5 patients had good to excellent and fair to poor outcomes, respectively, at 15 months postsurgery. Patients were divided into two groups (fair and poor vs. good and excellent outcomes at 15 months postsurgery), which significantly differed with respect to PSAV at 3 months postsurgery (P = 0.04), IPSS presurgery (P < 0.02), surgical length (P = 0.01), and hospitalization duration (P = 0.04). In a receiver operating characteristic analysis, the optimal cutoff value of PSAV of −0.52 ng/mL characterized effectiveness at 15 months after ThuLEP, and the area under the curve, sensitivity, and specificity were 0.82 (P < 0.02), 0.80, and 0.82, respectively. For PSAV <−0.52 and ≥−0.52 ng/mL, the percentages of reduction were, respectively, −78.6% and −71.4%, −33.3% and 0.0%, 94.4% and 40.0%, and −85.1% and −38.7% for IPSS, QoL, Qmax, and PVR, respectively. Conclusions Postsurgical PSAV was positively correlated with surgical success, and the PSAV cutoff was −0.52 ng/mL. PSAV can thus be used to guide postsurgical follow-up treatment at 3 months after BPH surgery.